THE INTENTION TO USE MOBILE BANKING DURING THE COVID-19 PANDEMIC: MODIFICATION OF THE UTAUT MODEL - Muhammad Hanif Ibrahim; Annes Nisrina Khoirunnisa; Uma Zalfa Salsabiil (Universitas Airlangga, 2022)
This study want to examine society's intentions towards mobile banking sharia in the ease of solving their financial problems. The increase in the use of smartphones makes the banking industry provide services mobile banking to facilitate and increase customer productivity, especially during the Covid-19 pandemic. Intention to use sharia mobile banking measured using the Unified Theory of Acceptance and Use of model Technology (UTAUT. Type this research uses quantitative research that is supported by data qualitative. The sampling technique used purposive sampling which was tested using the SEM-PLS analysis technique with an analytical tool, namely Warp-PLS 5.0 and exploratory analysis using SPSS 23. Results of SEM analysis shows that there is a good intention by the society in using mobile banking and the public finds it easy to operate to increase productivity. The implications of this research as input for the banking sector in terms of improving the quality of mobile banking so that people can produce during the Covid-19 pandemic.